An analysis of guidance and counseling programs - Rasyid, Mimi Gita Riskia; Aryani, Farida; Buchori, Sahril; Mansyur, Ahmad Yasser (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to examine: 1) the planning and implementation of guidance and counseling programs and 2) the supporting and hindering factors of the implementation of guidance and counseling programs. This study employed a qualitative approach with a descriptive design. Data analysis consisted of data reduction, data presentation, and conclusion drawing. The results showed that: 1) the guidance and counseling programs were planned and implemented optimally and professionally at MTsN 1 Makassar. However, at MTsN 2 Makassar, although planned, a few programs were not implemented; 2) the guidance and counseling programs at MTsN 1 were evaluated effectively and systematically, whereas at MTsN 2 Makassar, the programs were evaluated responsively and directively; and 3) no hindering factors were identified at MTsN 1 Makassar, and various supporting factors influenced the implementation of its guidance and counseling programs. In contrast, at MTsN 2 Makassar, several hindering factors were identified, and supporting factors were limited.